1998
DOI: 10.1002/(sici)1097-0142(19980415)82:8<1460::aid-cncr5>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with advanced gastric carcinoma with a 5-fluorouracil-based or a cisplatin-based regimen

Abstract: The efficacy of 5-FU, modulated with 6S-LV, is moderate in patients with advanced gastric carcinoma, similar to cisplatin-containing regimens. PS and other prognostic factors could influence the response rate, which does not appear to be a reliable parameter for evaluating the outcome of chemotherapy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…24,36 The decreased rate of HFS observed in our study might be due to the lower dose of capecitabine (850 mg/m 2 twice daily on days). [2][3][4][5][6][7][8][9][10][11][12][13][14][15] In summary, this study shows that mXELIRI is a safe and effective therapy for patients with AGC, with a manageable tolerability profile. XELIRI offers a simplified regimen that is less inconvenient for patients and avoids the discomfort and complications of the central venous access required with continuous infusion of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,36 The decreased rate of HFS observed in our study might be due to the lower dose of capecitabine (850 mg/m 2 twice daily on days). [2][3][4][5][6][7][8][9][10][11][12][13][14][15] In summary, this study shows that mXELIRI is a safe and effective therapy for patients with AGC, with a manageable tolerability profile. XELIRI offers a simplified regimen that is less inconvenient for patients and avoids the discomfort and complications of the central venous access required with continuous infusion of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…Current response rates to chemotherapy among advanced gastric cancer (AGC) patients are about 10% to 20% for a single agent and 30% to 50% for combination regimens. [3][4][5][6][7] New chemotherapeutic agents, including taxane, irinotecan, oxaliplatin, and S-1, have been introduced for the treatment of gastric cancer, and these drugs have shown promising response rates without sacrificing acceptable toxicity. [8][9][10] However, no regimen has been regarded as definitely superior to any other at present.…”
mentioning
confidence: 99%
“…More recently, the ECF combination regimen of CDDP, epirubicin (EPI), and infusional 5-FU proved very effective in phase II studies [14,15], and it was superior to FAMTX in terms of response rates (46% vs 21%; P = 0.0002) and overall survival (8.7 vs 6.1 months; P = 0.0005) in a randomized phase III comparison, with mild toxicity (16). Since then the combination of CDDP and infusional 5-FU, with or without EPI, has become the most widely used regimen in front-line chemotherapy for advanced gastric cancer, even though some authors have reported no signifi cant differences between CDDP and non-CDDP-containing regimens [17,18]. However, front-line chemotherapy for advanced gastric cancer has remained unsatisfactory, because overall survival does not generally exceed 10 months.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoropyrimidines may be considered a reference treatment for elderly patients with advanced gastric cancer, and most studies investigating these agents as monochemotherapy suggest that approximately 20% of patients are progression-free 6 months after treatment onset. [25][26][27][28] The hypothesis for the current study was that, using FOLFOX-4 as induction chemotherapy and LV/bolus and continuous infusion 5-FU as maintenance chemotherapy, at least 40% of patients would be progression-free 6 months after the start of chemotherapy. It was calculated that 33 patients should be recruited with a 0.05 level of significance and 80% power for correct selection of treatment (absolute difference in 6-month DCR of 20%), based on Simon's mimax design.…”
Section: Statistical Considerationsmentioning
confidence: 99%